2016
DOI: 10.18805/lr.v0iof.3548
|View full text |Cite
|
Sign up to set email alerts
|

AMMI and GGE biplot analysis of multi environment yield trial of soybean in North Western Himalayan state Uttarakhand of India

Abstract: The investigation was carried out to study Genotype × Environment (G×E) interaction for seed yield in 36 soybean genotypes including check PS1092 over 3 diverse environments represented by different altitudes in Uttarakhand. Grain yield performances of soybean genotypes were evaluated during Kharif 2013 season using a randomized complete block design. The AMMI analysis indicated that environment, genotypes and genotype by environment interactions had significantly affected seed yield and accounted for 9.76, 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 15 publications
6
26
0
2
Order By: Relevance
“…The results of this study imply that environment and GEI are important in controling the expression of yield trait (Gedif et al, 2014). Similar findings in the same crop were also obtained in various studies (Asfaw et al, 2009;Gurmu et al, 2009;Bueno et al, 2013;Atnaf et al, 2013;Jandong et al, 2011;Bhartiya et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study imply that environment and GEI are important in controling the expression of yield trait (Gedif et al, 2014). Similar findings in the same crop were also obtained in various studies (Asfaw et al, 2009;Gurmu et al, 2009;Bueno et al, 2013;Atnaf et al, 2013;Jandong et al, 2011;Bhartiya et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…GGE has been recognized and applied as a popular method to analyse and visualize the pattern of GEI in multi-environment yield trials in various crops (Brar et al, 2010;Jandong et al, 2011;Ullah et al, 2012;Bhartiya et al, 2017). However, the use of GGE biplot in Indonesia have not very much implemented, particularly as a tool for determining the mega environments, the best genotype in each location, and stability of soybean genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean genotype Himso1685 was found winner at Palampur and VLS 86 was found winner at Almora, Bajaura and Majhera and confirming the earlier study based on one year data in which both VLS 86 and Himso 1685 were found winner at Almora and Majhera location (Bhartiya et al 2016). Environments within the same sector share the same winning genotype or vice-versa (Farshadfar and Sadeghi 2014).…”
Section: Which-won-where and Mega-environment Identificationsupporting
confidence: 86%
“…Currently, the additive main effects and multiplicative interaction analysis (AMMI) have been widely used to quantify the genotypic effects of the GEI [6,7,8,9,10]. AMMI biplot analysis is defined as a useful tool to explore the GEI patterns [11] with simple graphic representation of genotypes and environments in a multivariate biplot [12].…”
Section: Introductionmentioning
confidence: 99%